New combinations and changes in the classification of Ceratopogonidae (Diptera, biting midges) - Borkent, Art (Zootaxa, 2015)
This short article contains some necessary taxonomic changes prior to the publication of a chapter on the Ceratopogonidae by the author for the upcoming Manual of Afrotropical Diptera and spearheaded by Ashley Kirk-Spriggs. Some additional placements of three genera to a recently redefined tribe are also included.